Changes in energy metabolism and intermittent sprint performance in healthy active individuals following a 6-week low carbohydrate eating plan - Pretorius, Johanna Mercia (Stellenbosch : Stellenbosch University, 2020)
Thesis (M Sport Sc)--Stellenbosch University, 2020.